Preflood Management Collaboration in Bandung District - Irfan Mauluddin; Herijanto Bekti; Ramadhan Pancasilawan (Universitas Padjadjaran, 2022)
This research is about the condition of the flood disaster in Bandung Regency, which is focused on the local government's steps to prevent, mitigate and prepare. The implementation of disaster management in Bandung Regency is regulated through the Bandung Regency government's policy with the establishment of the Regional Disaster Management Agency. The establishment of the Regional Disaster Management Agency based on the Bandung Regency Regional Regulation number 11 of 2010 concerning the establishment of the Bandung Regency Regional Disaster Management Agency organization, and the Bandung Regency Regent's Regulation number 53 regarding the details of the duties, functions, performance procedures of the Bandung Regency Regional Disaster Management Agency and followed by implementing regulations in the form of Regulations Bandung Regency area number 2 of 2013 concerning the implementation of Bandung Regency disaster management. The authors use common goals, division of roles, communication, and resources as the criteria for successful collaboration. This study uses a qualitative descriptive method where the data collection techniques used are library research and field studies consisting of observation and in-depth interviews.